2016
DOI: 10.1016/j.tips.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Neurosteroids for CNS Disorders

Abstract: Summary Neurosteroids are key endogenous molecules in the brain that affect many neural functions. Here, we describe recent advances in NIH-sponsored and other clinical studies of neurosteroids for CNS disorders. The neuronal GABA-A receptor chloride channel is one of the prime molecular targets of neurosteroids. Allopregnanolone-like neurosteroids are potent allosteric agonists as well as direct activators of both synaptic and extrasynaptic GABA-A receptors. Hence, neurosteroids can maximally enhance synaptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(173 citation statements)
references
References 119 publications
4
165
1
3
Order By: Relevance
“…We observed potent Zn 2ϩ blockade of neurosteroid-sensitive tonic currents but not phasic currents. A previous study reported inhibition of phasic currents by Zn 2ϩ (Ruiz et al, 2004); however, we demonstrate that neurosteroid-mediated GABA A receptor potentiation overcomes Zn 2ϩ depression of synaptic receptors. Because of the high affinity for ␦-containing receptors, Zn 2ϩ and neurosteroids influence inhibition through opposing action, albeit at different allosteric sites (Hosie et al, 2003 function may be quite different from its role in pathological states, such as epilepsy.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…We observed potent Zn 2ϩ blockade of neurosteroid-sensitive tonic currents but not phasic currents. A previous study reported inhibition of phasic currents by Zn 2ϩ (Ruiz et al, 2004); however, we demonstrate that neurosteroid-mediated GABA A receptor potentiation overcomes Zn 2ϩ depression of synaptic receptors. Because of the high affinity for ␦-containing receptors, Zn 2ϩ and neurosteroids influence inhibition through opposing action, albeit at different allosteric sites (Hosie et al, 2003 function may be quite different from its role in pathological states, such as epilepsy.…”
Section: Discussioncontrasting
confidence: 69%
“…Seizure experiments were conducted using hippocampus kindling model (Reddy and Mohan, 2011;Reddy et al, 2015). Mice were anesthetized by intraperitoneal injection of ketamine (100 mg/kg) and xylazine (10 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations